04.13 The transcription factor foxo3 differentially regulates the expression of proinflammatory genes in rheumatoid fibroblast-like synoviocytes. (1st March 2017) - Brandstetter, Bernhard; Dalwigk, Karoline; Vladimer, Gregory I; Steiner, Günter; Smolen, Josef S; Kiener, Hans P; Karonitsch, Thomas
Abstract : Objective: The transcription factor (TF) FOXO3 is known to integrate information from multiple upstream signals (eg, cytokines, oxidative stress, growth factors) in order to maintain tissue homeostasis during stress. Interestingly, although an association between a FOXO3 genotype (SNP) and the severity of rheumatoid arthritis (RA) was recently reported, the role of this TF in rheumatoid fibroblast-like synoviocytes (FLS) has not yet been investigated. Methods: With approval by the ethics committee synovial tissues from patients fulfilling the ACR/EULAR classification criteria for RA were obtained as discarded specimens following synovectomy. RA-FLS were isolated according to standard procedures. FOXO3 phosphorylation was determined by western blots. MK2206 was used to inhibit AKT. Nuclear-cytoplasmatic shuttling of FOXO3 was visualised and quantified by confocal immunofluorescence microscopy. FLS were transfected either with control or FOXO3 siRNA pools in order to investigate the role of FOXO3 in the TNF-induced inflammatory response. The expression of cytokines, chemokines and proteases, that are all known to be involved in RA pathogenesis, was assessed by ELISA, qPCR and western blots. Results: TNF, which is well known to be at the apex of the inflammatory cytokine network in RA, promoted the phosphorylation and nuclear export (inhibition) of FOXO3 in FLS. FOXO3 phosphorylation by TNF was inhibited by the AKT-inhibitor MK2206, demonstrating that TNF induces AKT phosphorylation to subsequently control FOXO3 activity in FLS. To further investigate the role of FOXO3 in the TNF-induced inflammatory response we silenced FOXO3 expression by using specific siRNA pools. Interestingly, while IL6 and IL8 expression was not affected by FOXO3 knockdown, a significant reduction in MMP3 expression was observed. In contrast, FOXO3 knockdown by siRNA promoted the TNF-induced expression of BAFF, TNFSF10 and CXCL11, suggesting that FOXO3 is a negative regulator of these genes. Conclusions: Our data reveal differential regulation of arthritis-associated genes by FOXO3 in FLS and thus support the idea that FOXO3 plays a crucial role in rheumatoid synovitis.